(untitled) (Indian Journal of Animal Production and Management, 2024)
The present study was carried out at Osmanabadi goat unit of Red Kandhari Research and Instructional Farm, College of Veterinary and Animal Sciences, Parbhani, MAFSU, for a period of 90 days. Eighteen Osmanabadi kids were divided into three treatment groups viz T0 (Thatch roof) T1 (Asbestos roof) T2 (FRP sheet roof). The variation in weekly pulse rate, respiration rate and body temperature were recorded in the morning and evening throughout the experiment. The results revealed that the thatch roof shed significantly (P<0.05) reduced pulse rate, respiration rate and body temperature of kids. The study concluded that thatch roof effectively improves environmental temperature and humidity than asbestos roof and FRP sheet roof shed.